Frequency of gestational diabetes mellitus and associated risk factors amongst women attending antenatal clinic at a tertiary care hospital of West Bengal, India - Rabi, Tousif; Bandyopadhyay, Kausik; Adak, Shiuli Roy (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Women with gestational diabetes are associated with adverse pregnancy outcomes. This study was conducted to evaluate prevalence of gestational diabetes mellitus and associated risk factors amongst women attending antenatal clinic of a tertiary care hospital of west Bengal, India. Methods: Universal screening for gestational diabetes mellitus was done in 215 women with estimated gestational age between 24 weeks to 28 weeks. They were requested to drink 75 gram of glucose dissolved 300 ml of water irrespective of their last meal. Gestational diabetes mellitus was diagnosed if 2 hour plasma glucose value was ≥ 140 mg/dl. Relevant history was taken and associations with risk factors like age, parity, pregnancy body-mass index, bad obstetric history, family history of diabetes and history of previous macrosomia were analysed statistically. Results: This study found that prevalence of gestational diabetes mellitus was 14.9%.Statistically significant association was found between glucose tolerance in pregnancy and maternal age, pregnancy body-mass-index, bad obstetric history, family history of diabetes and history of previous macrosomia. Conclusions: Prevalence of gestational diabetes mellitus was 14.9% which can be considered alarming and its associations with risk factors were statistically significant.